Growing Pains - S.M Mei Wulan (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Growing pains (GP) are common in children due to chilhood musculoskeletal pain. The prevalence ofgrowing pain ranges from 3-37% of children. GP have typical clinical characteristics, but the etiology andits development into non-inflammatory pain syndromes remain inconclusive. GP are not associated withserious organic disease and specific laboratory evidences. The most important action to take is to distinguishbetween benign and severe muskuloskeletal pain in children for addressing proper treatment. The mostappropriate intervention is to explain the natural course of GP, that are administering long acting analgetic atnight under certain circumstances, and applying heating pad, massage and stretching exercise during the day.Keywords: growing pain, benign musculoskeletal pain, non-inflamatory pain